Pelaksanaan Transaksi Perjanjian Jual Beli Hasil Panen Padi Secara Lisan di Desa Keban Jati Kecamatan Pasemah Air Keruh Kabupaten Empat Lawang - Septa Junisa; Siti Malikhatun Badriyah (Pusat Riset dan Inovasi Nasional, 2025)
A contract is an agreement by which two or more people bind themselves to each other, and one of the most common types of contract in everyday life is a sale and purchase. This sale and purchase agreement can be made in writing or verbally. In the community in Pasemah Air Keruh district, the oral agreement has become a custom and tradition that is used as a basis for making oral agreements. However, in oral agreements it is very vulnerable and easy for the parties to default and the legal force of this oral agreement is difficult to prove. The purpose of this research is to find out how the oral sale and purchase agreement of rice harvest is implemented by the community in Pasemah Air Keruh Subdistrict, and to find out how disputes are resolved when there is a default in the oral sale and purchase agreement in Pasemah Air Keruh Subdistrict. The method used in this research is Empirical Juridical. The method of analysis in this research uses qualitative methods. The results of this research are the implementation of the sale and purchase agreement carried out by the community of Pasemah Air Keruh Subdistrict based on trust and has become a habit in the community, this oral sale and purchase agreement is supported by an open system in Book III of the Civil Code, which adheres to an open system. The settlement of disputes that occur in the community of Pasemah Air Keruh Subdistrict is resolved by means of family consultation.